Optimization of Plant Performance at North American Palladium’s Lac Des Iles Mill Using Integrated Metallurgical and Mineralogical (Qemscan) Testing - Chris J. Martin; Nichola A. McKay (International Mineral Processing Congress, 2003)
"In mid-2001, North American Palladium commissioned a new 15,000 tonnes per day milling and flotation circuit at their Lac des Iles Mine (LDI), one of only two primary platinum group element (PGE) producers in North America. The mill treats an ore containing 2.3 g/t PGE producing a concentrate assaying 300 g/t PGE, at a recovery of roughly 75%.Top-size control crushing is conducted ahead of semi-autogenous milling. A portion of the SABC circuit feed is crushed to –25mm to increase mill throughput. Product from the SABC circuit is fed to flotation. Flotation consists of roughing and scavenging, with the rougher and scavenger concentrates each being reground using vertimills. Cleaner flotation uses two stages of cleaning using mechanical cells, and a third stage using flotation columns, the column tails being scavenged using a bank of mechanical cells. Rougher concentrate by-passes the first cleaner circuit. Reagents added include amyl xanthate collector, dithiophosphate promoter, MIBC frother and a carboxy methyl cellulose-based gangue depressant.SGS Lakefield Research, together with staff at LDI initiated a structured plant optimisation program comprising on-site testing, bench-scale flotation and mineralogical analysis using QemSCAN. The objectives of the mineralogical studies were 1) to identify feed PGM, their size distribution and mineral associations, 2) establish relationships between the PGM mineralogy and PGM floatability, and 3) characterize the culprit silicate minerals diluting the final concentrate.PGM flotation response at Lac des Iles is clearly bi-modal in nature, with about 60% of the PGM floating quickly, to a high value rougher concentrate. The mineralogical work was able to explain the causes of the bi-modal PGM floatability, which in turn created new opportunities for the metallurgists to optimise the circuit."